Visions, prophecies, and divinations : early modern Messianism and Millenarianism in Iberian America, Spain and Portugal - Megiani, Ana Paula Torres. (The Iberian Religious World, 2016)
Visions, Prophecies and Divinations is an introduction to the vast and complex phenomena of prophecy and vision in the Spanish and Portuguese Empires. This book is dedicated to the study of the millenarian and messianic movements in the early modern Iberian world, and it is one of the first collections of essays on the subject to be published in English. The ten chapters range from the analysis of Mesoamerican and South American indigenous prophetical beliefs to the intellectual history of the Luso-Brazilian Jesuit Antônio Vieira and his project of a Fifth Empire, passing through new approaches to the long-lasting Sebastianist belief and its political implications.